Geometrias hiperbólicas com uso do geogebra - Marcondes, Talita Melsone (2014)
This work has the purpose of bringing to the context of regular education (Secondary) non- Euclidean geometries, despite being covered in the Basic Education Curriculum Guidelines, are still left aside by most teachers. Two approaches were performed. Initially a historical approach is proposed to provide motivation to the study of non-Euclidean geometries. Finally an approach is proposed using GeoGebra, an educational geometry software to study basic concepts of hyperbolic geometry, such as a line, segment, angle and polygons.